Management innovation and firm performance: An integration of research findings. Issue 5 (October 2015) - Walker, Richard M.; Chen, Jiyao; Aravind, Deepa
Abstract While the effect of technological innovations (TI) on firm performance is established, the performance contributions of management innovations (MI) are as yet undetermined. Theoretical discourse on the motivation for the adoption of MIs questions their performance outcome, and an integration of empirical research of the MI-performance relationship is lacking. This study thus examines three questions: (1) is the adoption of MI beneficial to organizations; (2) is the impact of MI on performance at par with that of TI; and (3) what are the potential sources of inconsistency in the MI-performance relationship? We quantitatively integrated the empirical findings using 52 independent samples from 44 articles published in peer-reviewed journals via two different procedures―support score and meta-analysis―for complementarity and reliability. The results from both procedures indicate that: (1) MI positively affects performance; (2) the direction and strength of the effect of MI on performance does not differ from that of TI; and (3) industrial sector (manufacturing vs service) and construct measurement (both innovation and performance) moderate the MI-performance relationship. We discuss the implications of our findings for future research on innovation and performance in organizations.